Reconstructing Sexual Education: Social Construction of Islamic Sexuality Knowledge Through Taulebih.id Platform - Bilbina Iqlima Putri; Nurul Fatimah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The increase in cases of sexual violence, including in digital spaces, underscores the urgency of comprehensive and value-based sexual education. This study aims to analyze the role of the Taulebih.id platform in building Islamic-based sexual knowledge. The research uses a qualitative approach through netnography methods, platform observation, and in-depth interviews with four informants consisting of active followers and the platform's public relations staff. Data collection was conducted from August to November 2024. The results of the study indicate that Taulebih.id contributes to building users' sexual knowledge through processes of externalization, objectification, and internalization. Programs such as Taulebih Goes To You, Period at Peace, and Knowlunteers provide collaborative spaces, safe spaces for women, and active user participation that strengthen collective awareness and critical understanding of sexuality issues. This process encourages the formation of a new reality of sexuality in digital spaces. Islamic values serve as a framework that allows taboo issues to be discussed more openly and socially accepted. These findings indicate that value-based digital platforms are effective as public education media in addressing sexual violence issues.